Pendidikan Sains dalam Membangun Karakter Masa Depan Peserta Didik di Sekolah Dasar - Sukarto Sukarto; I Wayan Suastra; I Made Citra; Ida Bagus Putrayasa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to explore the contribution of science education in building the future character of elementary school students. The method used is a literature review by analyzing relevant studies related to science education, character development, and 21st-century learning. The results indicate that science education based on the development of critical thinking, creativity, and collaboration skills positively contributes to shaping responsible, environmentally aware, and adaptive students. In conclusion, science education plays a strategic role in developing students’ future character through active and meaningful learning. Keywords: Active Learning, Elementary School, Future Character, Science Education, Students